5(x-2)=-9(x+1)+17

Simple and best practice solution for 5(x-2)=-9(x+1)+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-2)=-9(x+1)+17 equation:


Simplifying
5(x + -2) = -9(x + 1) + 17

Reorder the terms:
5(-2 + x) = -9(x + 1) + 17
(-2 * 5 + x * 5) = -9(x + 1) + 17
(-10 + 5x) = -9(x + 1) + 17

Reorder the terms:
-10 + 5x = -9(1 + x) + 17
-10 + 5x = (1 * -9 + x * -9) + 17
-10 + 5x = (-9 + -9x) + 17

Reorder the terms:
-10 + 5x = -9 + 17 + -9x

Combine like terms: -9 + 17 = 8
-10 + 5x = 8 + -9x

Solving
-10 + 5x = 8 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-10 + 5x + 9x = 8 + -9x + 9x

Combine like terms: 5x + 9x = 14x
-10 + 14x = 8 + -9x + 9x

Combine like terms: -9x + 9x = 0
-10 + 14x = 8 + 0
-10 + 14x = 8

Add '10' to each side of the equation.
-10 + 10 + 14x = 8 + 10

Combine like terms: -10 + 10 = 0
0 + 14x = 8 + 10
14x = 8 + 10

Combine like terms: 8 + 10 = 18
14x = 18

Divide each side by '14'.
x = 1.285714286

Simplifying
x = 1.285714286

See similar equations:

| 12/21=18/x | | 66+30x=360+30x | | (5x+5)(5x^2+3x+2)= | | 3(4z+3)= | | -3(7.5+-3y)-2y=5.5 | | 6/5 | | 23-13=2(x-8) | | 4d-5(d-1)=3-d+2 | | 3p+5=p+15 | | 6/7(-4/9-1/7x)=-62/147 | | X=3-12 | | -12y+10=46 | | 5+7x+16+x=11x-3-x | | 6k+5=20 | | 9y^2-12y-1=0 | | h(t)=20-16t*2+32t | | 12s=8+2x(5s+3) | | 5(x-4)=-7(x+3)+45 | | 11x^2(144)=0 | | 3j^2-20j=12 | | 2x-9+87-9x*9+1=100 | | 9x*lnx+x=0 | | 27=3d | | 12s=8+10s+6 | | x^2+10x+14=8 | | 11x^2-55x=0 | | (2x^2-4y)dx+(-4x-y^4)dy=0 | | 5(2x+4)=37 | | 25=2h+5 | | 50n^2+315n+405=0 | | ln*3x-ln*10=4 | | 4t^3-24t^2-36t=0 |

Equations solver categories